AKTIVITAS BELAJAR DAN PEMAHAMAN KONSEP MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DI KELAS XI MIPA SMA N 5 BUKITTINGGI TAHUN PELAJARAN 2019/2020 - Rahmah, Novetri; Imamuddin, M; Rahmat, Tasnim (Math Educa Journal, 2020)
This research is motivated by the lack of student activity in the learning process and the low ability to understand students' mathematical concepts. This is contrary to learning that is still conventional in nature, namely the learning process issued by the teacher. To overcome this problem, the Think Talk Write (TTW) cooperative learning model is applied. Mathematics learning for students who learn to think to talk cooperative learning models (TTW) and understanding mathematical concepts who learn think to talk cooperative learning models (TTW) are better for those looking for conventional learning. This type of research is a pre-trial research design that is the Static Group Comparison Design. The population in this study were all class XI MIPA. The sample in this study was class XI MIPA 2 as an experimental class and class XI MIPA 1 as a control class. The instrument used in the study was an observation sheet and a concept understanding test consisting of essay tests. Data obtained from the results of the study concluded that student activity with the cooperative learning model think talk writes (TTW) was 69.75%, so the activity was classified as active. Based on data analysis using t-test, it can be denied that "The ability to understand the mathematics of students who use the cooperative learning model of the type of think talk write (TTW) is better than conventional learning in class XI MIPA SMA N 5 Bukittinggi 2019/2020 academic year".